Gene expression profiling in normal cytogenetic acute myeloid leukaemia of Malay patient (Bangladesh Journal of Medical Science, 2021)
Background: Insight into recent molecular analyses of patients with acute myeloid leukaemia (AML) and a normal cytogenetic have revealed a striking heterogeneity with regard to the presence of acquired changes in gene expression. Nano String technology which is aimed to identify descriptive profiling of normal cytogenetic AML in differentially expressed genes involved in the different pathways in normal cytogenetic AML patients.Materials and method: Blood samples were obtained from eight at diagnosis patients with normal cytogenetics AML, two follow-up patients and two normal healthy controls prior to RNA extractions. RNA gene expression assay was performed using Nano Stringn Counter® Pan Cancer Pathway Panel (Nanostring Technologies, Seattle, Washington). Briefly, 100 ng of each total RNA sample was used as input into then Counter Pan Cancer Pathway Panel sample preparation. Data was extracted using then Counter RCC Collector and raw data output was imported into nSolver v2.6 analysis software for data analysis.Results: The age range was from 13-69 years, with a median age-range of 41 years. We found the most enriched up regulated genes in newly diagnosed normal cytogenetic AML enlisted MPO (7.25 log FC), FLT3 (5.02 log FC), MYCN (4.99 log FC), MYB (4.74 log FC), ITGA9 (4.48 log FC), KIT (4.41 log FC), MCM2 (3.47 log FC), RAD51 (3.40 log FC), CCNA2 (3.37 log FC) and PROM1 (3.24 log FC) which those commonly be found in AML cases. For highly expressed down regulated genes were GZMB (-5.80 log FC), IL8 (-5.79 log FC), TNFRSFSF10C (-5.03 log FC), LEF1 (-4.82 log FC), IL2RB (-4.70 log FC), IL7R (-4.44 log FC), BCL2A1 (-4.15 log FC), RASGRP1 (-4.13 log FC), IL1R2 (-4.00 log FC) and HSPA6 (-3.99 log FC).Discussion and conclusion: Nano String required smaller amounts of starting material, and can perform mRNA expression profiling with digital precision, therefore the results do not require further validation by another method. MPO expression was significantly associated with disease-free survival (DFS). Previous report demonstrated that the groups by the MPO expression in the intermediate cytogenetic risk group showed a significant difference in DFS (p